Inoculation With a Microbe Isolated From the Negev Desert Enhances Corn Growth - Khan, Noor; Martínez-Hidalgo, Pilar; Humm, Ethan A.; Maymon, Maskit; Kaplan, Drora; Hirsch, Ann M. (Frontiers in Microbiology, 2020)
Corn (Zea mays L.) is not only an important food source, but also has numerous uses, including for biofuels, fillers for cosmetics, glues, and so on. The amount of corn grown in the U.S. has significantly increased since the 1960’s and with it, the demand for synthetic fertilizers and pesticides/fungicides to enhance its production. However, the downside of the continuous use of these products, especially N and P fertilizers, has been an increase in N2O emissions and other greenhouse gases into the atmosphere as well as run-off into waterways that fuel pollution and algal blooms. These approaches to agriculture, especially if exacerbated by climate change, will result in decreased soil health as well as human health. We searched for microbes from arid, native environments that are not being used for agriculture because we reasoned that indigenous microbes from such soils could promote plant growth and help restore degraded soils. Employing cultivation-dependent methods to isolate bacteria from the Negev Desert in Israel, we tested the effects of several microbial isolates on corn in both greenhouse and small field studies. One strain, Dietzia cinnamea 55, originally identified as Planomicrobium chinensis, significantly enhanced corn growth over the uninoculated control in both greenhouse and outside garden experiments. We sequenced and analyzed the genome of this bacterial species to elucidate some of the mechanisms whereby D. cinnamea 55 promoted plant growth. In addition, to ensure the biosafety of this previously unknown plant growth promoting bacterial (PGPB) strain as a potential bioinoculant, we tested the survival and growth of Caenorhabditis elegans (a test for virulence) in response to D. cinnamea 55. We also looked for genes for potential virulence determinants as well as for growth promotion.